2014
DOI: 10.1097/qad.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid metabolomics reveals altered waste clearance and accelerated aging in HIV patients with neurocognitive impairment

Abstract: Objective(s):HIV-associated neurocognitive disorders (HAND) remain prevalent in HIV-infected patients on antiretroviral therapy (ART), but the underlying mechanisms are unclear. Some features of HAND resemble those of age-associated cognitive decline in the absence of HIV, suggesting that overlapping mechanisms may contribute to neurocognitive impairment.Design:Cross-sectional analysis of cerebrospinal fluid (CSF) from 100 individuals (46 HIV-positive patients and 54 HIV-negative controls).Methods:Untargeted C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 92 publications
5
107
0
2
Order By: Relevance
“…Nonetheless, these observations strongly suggest a plausible link between IFNγ-induced accelerated immunoproteasome-mediated HO-1 degradation in astrocytes and brain HO-1 loss in HIV-infected individuals with HAND. This potential mechanism is particularly relevant in light of recent reports of a correlation between the presence of IFNγ-secreting CD8+ T lymphocytes and increased IFNγ in CSF and the diagnosis of HAND in HIV-infected individuals (Cassol et al 2014; Schrier et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these observations strongly suggest a plausible link between IFNγ-induced accelerated immunoproteasome-mediated HO-1 degradation in astrocytes and brain HO-1 loss in HIV-infected individuals with HAND. This potential mechanism is particularly relevant in light of recent reports of a correlation between the presence of IFNγ-secreting CD8+ T lymphocytes and increased IFNγ in CSF and the diagnosis of HAND in HIV-infected individuals (Cassol et al 2014; Schrier et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Early studies indicated that older individuals were at increased risk for HAND (Cherner et al, 2004). Additional evidence that HAND is due at least partially to accelerated aging includes studies of CSF metabolomics (Cassol, Misra, Dutta, Morgello, & Gabuzda, 2014), in vitro analysis in astrocytes(Ojeda et al, 2014), and neurophysiological studies (Chang, Holt, Yakupov, Jiang, & Ernst, 2013; Holt, Kraft-Terry, & Chang, 2012). Still, in clinical samples telomere length has not been consistently associated with neurocognitive impairment or other indicators of neuroHIV (Giesbrecht et al, 2014; Malan-Muller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing efforts to apply high-throughput analyses to microRNA expression in brain and plasma represent exciting opportunities to gain insights in disease pathogenesis and perhaps establish new biomarkers for disease [105][106][107][108]. Similarly, metabolomics approaches using nuclear magnetic resonance and mass spectrometry [11,109] have been applied successfully to studying neurological infections and herald a new epoch in diagnosing and understanding these devastating diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%